The use of ELISA is comparable to immunoprecipitation in the detection of selected myositis-specific autoantibodies in a European population - Loganathan, Aravinthan; McMorrow, Fionnuala; Lu, Hui; Li, Danyang; Mulhearn, Ben; McHugh, Neil John; Tansley, Sarah Louise (Frontiers in Immunology, 2022)
Background: The reliable detection of myositis-specific autoantibodies provides valuable clinical information regarding prognosis, clinical progression and diagnostic confirmation. Objectives: To evaluate the accuracy of a commercial ELISA immunoassay in detecting myositis-specific autoantibodies in comparison to immunoprecipitation as the reference standard. Methods: Serum samples were chosen from a biobank of more than 3000 samples. Samples with a confirmed MSA on IP (n=116) were evaluated in duplicate by ELISA to detect Mi2, MDA5, Jo1, EJ, KS, PL-7 and PL-12 (Medical & Biological Laboratories Co. Ltd, Nagoya, Aichi, Japan). Healthy controls samples (n=116) confirmed autoantibody negative by immunoprecipitation were similarly assessed. Results: There was a very good agreement between ELISA and immunoprecipitation for serum samples containing anti-Mi2, MDA5, Jo1, EJ, KS and PL-7 and PL-12 auto-antibodies. Cohen’s κ values ranged from 0.86-1 for the measured autoantibodies on ELISA. Conclusion: ELISA was an accurate method for detecting anti-synthetase, anti-Mi2 and anti-MDA5 autoantibodies.